Fuzzy Control Systems with Time-Delay and Stochastic Perturbation Analysis and Synthesis - Wu, Ligang; Su, Xiaojie; Shi, Peng.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents up-to-date research developments and novel methodologies on fuzzy control systems. It presents solutions to a series of problems with new approaches for the analysis and synthesis of fuzzy time-delay systems and fuzzy stochastic systems, including stability analysis and stabilization, dynamic output feedback control, robust filter design, and model approximation. A set of newly developed techniques such as fuzzy Lyapunov function approach, delay-partitioning, reciprocally convex, cone complementary linearization approach are presented. Fuzzy Control Systems with Time-Delay and Stochastic Perturbation: Analysis and Synthesis is a comprehensive reference for researcher and practitioners working in control engineering, system sciences and applied mathematics, and is also a useful source of information for senior undergraduates and graduates in these areas. The readers will benefit from some new concepts, new models and new methodologies with practical significance in control engineering and signal processing.    .
Analysis and Synthesis of T-S Fuzzy Time-Delay Systems -- Analysis and Synthesis of T-S Fuzzy Stochastic Systems -- Fuzzy Control Applications.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence